GERMINATION OF SCLEROCARYA BIRREA SEEDS: A TREE OF MEDICINAL IMPORTANCE - Moyo, M.; Kulkarni, M.; Finnie, J.; Van Staden, J. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Sclerocarya birrea (marula) is used in many African countries for a number of ailments. The bark decoctions are administered as enemas in treating malaria and diarrhoea. Some tribes use bark for treating fevers, stomach complaints and ulcers, and roots for sore eyes. Fresh leaves are chewed for indigestion and infusions or decoctions are drunk for diabetes. The fruit has a delicious pulp with high vitamin C. Though some attempts are being made to domesticate this high-value indigenous plant, there is limited information on the aspects of seed germination. The objective of this study was to investigate the role of light, temperature, cold stratification and dry storage on the germination of S. birrea. Temperatures between 25-35°C favoured germination of opercula-removed seeds under continuous dark conditions. White light inhibited the germination of opercula-removed seeds. The inhibitory effect of light was reversed when seeds were transferred to dark conditions. This photoinhibition effect on opercula-removed seeds was lost after 12 months of storage at room temperature. Cold stratification (5°C) for 14 days significantly improved germination (66%) as compared to non-stratified seeds (32%). Seeds of S. birrea can be considered as orthodox as they tolerated desiccation without significant loss of viability. Both intact and opercula-removed seeds readily imbibe water suggesting physiological rather than physical dormancy. This study indicates that after-ripening and seed maturation are critical factors for germination of S. birrea.